Design Modification of the Horizontal Tail and Performance Simulation of LSU-05NG Drone - A Vianto; S Tobing; K Hidayat (AVIA, 2021)
LSU-05NG is a drone manufactured and developed by LAPAN. The horizontal tail of the aircraft is used to maintain longitudinal stability, however, there has been no study on a tail modification that could improve the performance. The study of tail modification will examine the impact of modifying the airfoil to NACA 2412 and NACA 63-215. The base model of LSU-05NG uses NACA 0012 as the airfoil profile which is used in the horizontal tail. The performance is measured from the value of the lift coefficient, drag coefficient, and longitudinal stability. The results are obtained using ANSYS CFX Software. Based on the study, the modification of the horizontal tail has no impact on the lift and drag coefficient, however, impacts greatly on the pitching coefficient which determines the longitudinal stability. The airfoil profile that produces the highest longitudinal stability is NACA 63-215, followed by NACA 2412, and the last is the basic model using NACA 0012